Analisis Kinerja Konsultan Perencana Pada Proyek di Kalimantan Selatan - Gusti Eddy Mulya Marwizy (Lambung Mangkurat University Press, 2022)
The purpose of this study was to determine the factors that influence the performance of the planning consultant and to develop recommendations for improvement of these factors. There are 4 aspects that measure its performance, namely; 1) quality of planning documents, 2) aspects of planning time, 3) aspects of planning costs and 4) aspects of terms of reference. Therefore, this study uses 2 analytical methods, namely customer satisfaction index (CSI) importance-performance analysis (IPA). The results of the study indicate that there are several factors that affect the performance of the planning consultant and require priority handling, namely: (1) quality of planning documents: consistency between drawing documents, RKS, and engineer estimates, systematic presentation of design documents and considerations of technology availability and capabilities; and (2) terms of reference which consist of: data collection, spatial program structure, architectural design feasibility, final planning report, suitability of work experience with the position occupied. The recommended handling solution to overcome the performance problems of this planning consultant is to improve the competence of human resources. Human resources include planning consultants, architects and all parties involved in the project planning process, both institutionally managing and improving the management of the implementation of the planners.